The interplay between heart rate variability, inflammation, and lipid accumulation: Implications for cardiometabolic risk - Cameron R. Wiley; Vida Pourmand; Sarah K. Stevens; Marc N. Jarczok; Joachim E. Fischer; Dario Boschiero; Eleonora Poggiogalle; Julian Koenig; Julian F. Thayer; DeWayne P. Williams (Physiological Reports)
Abstract Deleterious adiposity (e.g., obesity) is considered an inflammatory condition that increases risk for cardiovascular diseases. Lower heart rate variability (HRV), an independent predictor of cardiovascular disease risk, is linked with higher levels of adiposity and inflammation. However, indices of adiposity vary in their strength of association with disease risk. Body mass index (BMI) is a modest predictor of disease, while the lipid accumulation product (LAP) better predicts disease risk. The current investigation used cross‐sectional and prospective designs to probe the differential associations between HRV and multiple measures of adiposity (e.g., LAP and BMI) and examine if inflammation (measured via C‐reactive protein; CRP) mediated these associations. Study 1 showed that HRV was more strongly linked with LAP relative to other adiposity measures and that this link was mediated by CRP. Study 2 replicated Study 1 results and showed that this association remained significant 4 years later. Our novel findings are consistent with studies suggesting LAP may be a superior measure of cardiovascular disease risk relative to other measures of adiposity. Importantly, the strong link between HRV and LAP was mediated by inflammation, highlighting the key role of the cholinergic anti‐inflammatory pathway in regulating obesity and associated health consequences.